BUSINESS INTELEGENCE MONITORING SYSTEM OF MEDICINE AND MEDICAL EQUIPMENT INVENTORY AT BAPTIS BATU MALANG HOSPITAL - Maulidina Rahmawati Surya (Universitas Trunojoyo Madura, 2021)
An increase in the income level of the population causes the demand for health services to increase and affects the increase in the cost of health services. This needs to be balanced with the increasing public health status. One of the improvement processes is by implementing the BI system in the Batu Baptist Hospital Pharmacy. The method used is implementing the BI system at Batu Baptist Hospital to support quality in strategic decision making. The BI system for drug and medical equipment inventory can be accessed by two types of users, namely admin and warehouse manager/pharmacist. Each of these actors can operate the system according to the access rights they have. Admin can make ETL, and manage BI System dashboard for medicine and medical equipment inventory. The results of the dashboard can later be seen by the warehouse manager/pharmacist. BI development to assist decision making at Batu Baptist Hospital Malang through several stages: data warehouse modeling, ETL process, pentaho application connection with tables, and BI dashboard visualization design. The BI dashboard that has been visualized is a graph of the comparison of drugs and outgoing drugs, a comparison graph of medical device supplies and the use of medical devices, trend graphs so that the expenditure of medical devices in a given month can be used as a manager's consideration for adding medical equipment supplies based on the needs of the most widely used medical equipment. per month in one year.